Strategi Pemasaran Pariwisata Sembalun Kecamatan Sembalun Kabupaten Lombok Timur Nusa Tenggara Barat - Virgilenna, Sinta; Anom, I Putu (JURNAL DESTINASI PARIWISATA, 2018)
The number of tourist arrivals during the low season tends to decline. It also has an impact on sightseeing. Therefore, marketing strategy is very important to be able to increase the number of tourist visit to be able to compete with other tourism object and can give positive impact for society Sembalun. Sembalun tourism is located on Jalan Wisata Rinjani, Sembalun Bumbung, Kab. East Lombok Kec. Sembalun, Sembalun Village of West Nusa Tenggara. This study aims to determine the marketing mix, and marketing strategy at Sembalun Tour. The data collection in this research is done by observation, in-depth interview, document and literature study. The determination of informants was determined on the basis of random purposive sampling in which subjects were chosen on the basis of specified criteria. These criteria are Sembalun tourism managers and communities around Sembalun East Lombok. The result of this research is marketing mix at Sembalun tourism based on product, price, distribution channel, promotion, person, physical proof and process. In this research also discuss about SWOT analysis about the strengths, weaknesses, opportunities and threats that are owned by Sembalun tourism which is related to mix mix (marketing mix), from marketing strategy that is Increase promotion to other market, Increase cooperation with Travel agent good Outside and inside the country, improve access, improve the quality of human resources.   Keyword : Management, Marketing Mix, Marketing Strategy , Sightseeing Tour